Hemangioma of the Atherosclerotic Changed Aortic Valve - A. van Broekhoven; P. A. J. Krijnen; H. W. M. Niessen; A. B. A. Vonk (Case Reports in Cardiology)
The incidence of heart valve hemangioma is very low and is mostly observed in the mitral and tricuspid valve. In 2006, two cases of aortic valve hemangioma were reported for the first time, including one with calcifying aortic valve stenosis. We now present a case of aortic valve hemangioma in a patient suffering from aortic valve insufficiency combined with atherosclerotic thickening.